Analisis Efektivitas Pendapatan Asli Daerah dan Dana Perimbangan di Kabupaten Kerinci Tahun 2011 – 2016 - Murniati Murniati (J-MAS (Jurnal Manajemen dan Sains), 2018)
This research entitled the effectiveness of Revenue Equalization Fund and regional Original in Kerinci 2011-2016 Year, with the aim to find out how large the original revenue growth areas and Fund Balances in the Regency of Kerinci 2011-2016 Year and To find out how large a rate Efekstivitas the original Revenue Equalization Fund and Areas in Kerinci 2011-2016 Year. This research dalaksanakan in the District of Kerinci using Secondary data, with data collection techniques Research Library with Descriptive method quantitative and qualitative descriptive. As for the analysis tools used i.e. the ratio of the growth and the ratio of effectiveness. Based on the results of the study showed that the original receipt of an income Growth Areas in the Regency of Kerinci from year 2011 – 2016 is always increasing. While the percentage of growth experiencing fluctuations. The average nominal Target for 6 years 2011-2016 years of Rp. 49,597,954,211, where the average target percentase 2011-2016 year of 17.79%. Growth targets and the realization of Equalization Funds in the Regency of Kerinci, explained that in nominal target of receiving funds from the balance of the year 2011 – 2016 in total amounting to Rp.  3.767.521., 800.135,20 average per year or Rp. 627,920,300,022.53. So also with the percentage growth target receiving funds Balances experienced fluctuation that is 20.53% average. Whereas the effectiveness of the original Income Areas in the Regency of Kerinci Years 2011-2016, an average realization of greater than the target which entered criteria very effectively with the value of the average of 105.79%. The effectiveness of the Equalization Funds in the District of Kerinci 2011-2016 Years, on average exceeds its realization of targets set. It means that by the criterion of effectiveness including the categories very effectively with an average effectiveness of 100.39 percentasi%. Keywords: effectiveness, Revenue Equalization Fund and regional Original